Penatalaksanaan Fisioterapi pada Osteoarthritis Genu Dextra dengan Modalitas Transcutaneous Electrical Nerve Stimulation (TENS), Ultrasound dan Terapi Latihan - Dwito Auliandra; Maya Triyanita (Pusat riset dan Inovasi Nasional, 2025)
Osteoarthritis of the knee is a degenerative condition of the knee joint characterized by the thinning of cartilage, leading to friction between the femur and tibia. This condition results in pain, limited joint mobility, and reduced strength of the quadriceps and hamstring muscles. Physiotherapy plays a crucial role in reducing these symptoms through modality-based approaches and structured exercise therapy. This study is a case study involving a single patient with right knee osteoarthritis. Data were collected through direct observation and evaluation of therapeutic outcomes. Interventions were conducted over four sessions using Transcutaneous Electrical Nerve Stimulation (TENS) to reduce pain, Ultrasound to enhance blood circulation and reduce inflammation, and exercise therapy focusing on improving muscle strength and joint range of motion. After four therapy sessions, there was a reduction in pain intensity, improved strength of the quadriceps and hamstrings, and increased joint range of motion. These results demonstrate that the combination of TENS, ultrasound, and exercise therapy is effective in improving function and quality of life for patients with right knee osteoarthritis. This study emphasizes the importance of a multimodal physiotherapy approach in managing chronic musculoskeletal disorders.